Ayat-Ayat Mengenai Air Perspektif Al-Qur’an: Studi Analisis Semantik Model Ensiklopedik - Iqrimatunnaya, Iqrimatunnaya (Jurnal Riset Agama, 2024)
The urgency of knowing the meaning of water from the Al-Qur'an perspective is the aim of this research. Using an encyclopedic model of semantic analysis and applying descriptive-analytical methods certainly makes this research classified as qualitative research. The formal object of this research is the knowledge of the Qur’an, while the material object is the verse about water. It was found that the word ماء, which means water, according to Qur'anic Software, contains 44 words with 10 forms in the Al-Qur'an. There has been a slight shift in the meaning of the word ma'. It started positive during the period of ignorance, then shifted slightly to become negative during the time of the Qur’an.